The Adequacy of the Islamic Institutes Teachers Efficiency in Constructing Achievement Tests According to Good Test Criteria from Their Perspective - Albadi, Badar Hamed Humaid; Al-Hidabi, Dawood Abdulmalek Yahya (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the efficiency of Islamic Institutes teachers in constructing achievement tests according to good test criteria. The sample of the study consisted of (43) teachers in the six Islamic institutes. In order to achieve the objective of the study, a (60) items questionnaire was developed and was divided into six axes: aims setting and test planning, items drafting, test outlining, test correction, test application, and analyzing and interpreting of test results. The efficiency of Islamic Institutes teachers in constructing achievement tests according to good test criteria was high by the average of (4.08). Three axes were of high level: test outlining, test correction, and test application. The axes of aims setting and test planning, items drafting were of high level, too; however, the axis of analyzing and interpreting of test results was of medium level. The study found that experience years had no effect on the efficiency in constructing achievement tests according to good test criteria. The study recommends encouraging the institutes’ teachers to work on analyzing and interpreting test results to benefit from test results in order to improve the teaching process.